2020
DOI: 10.1001/jama.2020.11413
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Industry Payments to Physicians in the United States From 2014 to 2018

Abstract: Author Contributions: Drs Ahlberg and Stephansson had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 3 publications
1
45
0
Order By: Relevance
“…Marshall et al found that since the launch of the US Open Payment Database, the total and annual average payment value per physician declined by −1.7% and −0.6%, respectively (ref. [34]). However, pharmaceutical companies increasingly prioritized the payments to hematologists and oncologists, with a 4.9% and 1.7% annual increase in total value and average payments (ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marshall et al found that since the launch of the US Open Payment Database, the total and annual average payment value per physician declined by −1.7% and −0.6%, respectively (ref. [34]). However, pharmaceutical companies increasingly prioritized the payments to hematologists and oncologists, with a 4.9% and 1.7% annual increase in total value and average payments (ref.…”
Section: Discussionmentioning
confidence: 99%
“…(ref. [20, 33, 34]) As several pharmaceutical companies disaffiliated from the JPMA and newly joined the JPMA, among all 92 companies, there were 18 companies without payment data over the four years. Thus, the average and median payments for each year and the trend of payments were calculated based on payments from all 92 companies and 74 companies with payment data for the four years between 2016 and 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have been conducted analyzing specialty-specific payment patterns between industry and physicians using the Open Payments database including but not limited to studies on orthopedic surgeons [ 12 ], emergency physicians [ 13 ], pediatricians [ 14 ], neurosurgeons [ 15 ], otolaryngologists [ 18 ], cardiologists [ 19 ], and ophthalmologists [ 20 ]. Additional research has also been conducted to further examine potential physician bias and conflicts of interest within particular specialty areas [ 21 23 ]. A recent systematic review also found that a large majority of studies found a positive association between industry payments and increased prescribing, including temporal and dose-response relationships [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Companies identified based on whether they disclosed opioid-related marketing payments in the CMS Open At the same time, nearly all large pharmaceutical companies have been involved in settlements related to off-label promotion, largely related to violations of the False Claims Act [3]. Past settlements and government transparency initiatives have contributed to our understanding of marketing [2,4]. The patterns of aggressive marketing identified in opioid settlements, which include downplaying drug risks, promoting use in vulnerable populations, marketing for unapproved indications, and providing financial inducements to providers, are not novel and have been previously documented in settlements related to illegal promotion of antipsychotics, gabapentinoids, antidepressants, and others [3].…”
Section: The Need For Ongoing Skepticism Of Pharmaceutical Marketingmentioning
confidence: 99%
“…In spite of public attention, litigation, and transparency initiatives, pharmaceutical industry marketing remains a widespread strategy for promoting new products to clinicians. Pharmaceutical company payments to physicians have remained largely stable in the past half-decade, totaling nearly $2 billion annually with 45% of physicians receiving such payments in 2018 [4]. At the same time, court cases have challenged the enforcement of longstanding requirements under the Food, Drug, and Cosmetic Act's requirements that companies demonstrate safety and efficacy data for off-label promotion [5].…”
Section: The Need For Ongoing Skepticism Of Pharmaceutical Marketingmentioning
confidence: 99%